Kaiso protects human umbilical vein endothelial cells against apoptosis by differentially regulating the expression of B-cell CLL/lymphoma 2 family members - Xiaodong Xue (Nature Portfolio, 2017)
Abstract Endothelial cell injury can promote the development of various cardiovascular diseases, thus, fully understanding the mechanisms underlying the maintenance of vascular endothelial cell homoeostasis may help prevent and treat cardiovascular disease. Kaiso, a zinc finger and BTB domain containing transcription factor, is key to embryonic development and cancer, but how Kaiso interacts with vascular endothelium is not fully understood. We report that Kaiso has an anti-apoptotic function in human umbilical vein endothelial cells (HUVECs) and human microvascular endothelial cells (HMEC-1s). Overexpression of Kaiso significantly increased cell viability and inhibited hydrogen peroxide-induced apoptosis. Furthermore, Kaiso increased expression of B-cell CLL/lymphoma 2 (BCL2) and reduced expression of BCL2-associated X protein (BAX) and BCL2-interacting killer (BIK) by differentially regulating gene promoter activity. Methylated DNA and specific Kaiso binding site (KBS) contributed to gene regulatory activity of Kaiso. In addition, p120ctn functioned cooperatively in Kaiso-mediated transcriptional regulation.